PENGARUH PENERAPAN ETIKA TERHADAP PENINGKATAN PROFESIONALISME AKUNTAN PUBLIK PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU - Rifayani, Desiyanti; Triwahyuni, Nadia; Nurfitriani, Nurfitriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Empirically, this research aims to examine the effect of implementing ethical rules in increasing the professionalism of public accountants. This research was conducted at 8 Public Accounting Firms in Pekanbaru. It was conducted by distributing 66 questionnaires. The analytical tool used in this research was multiple regression. Based on the data analysis and discussion, the results of this research showed that the application of independence, integrity and objectivity, the application of responsibility to colleagues, and the application of other responsibilities and practices have an effect in increasing the professionalism of public accountants. On the other hand, the application of responsibility to clients has no significant effect in increasing professionalism of public accountants at public accounting firms in Pekanbaru. Keywords: independence, objectivity, integrity, responsibility, profesionalism.